Comparison of dual- and single-source dual-energy CT in head and neck imaging - May, Matthias; Wiesmüller, Marco; Heiß, Rafael; Brand, Michael; Brügel, Joscha; Uder, Michael; Wüst, Wolfgang (European Radiology, 2019)
Objectives: The aim of this study was to compare image quality of single-source dual-energy CT (SS-DECT) with third-generation dual-source dual-energy CT (DS-DECT) in head and neck cancer. Materials and methods: One hundred two patients with histologically proven head and neck cancer were prospectively randomized to undergo radiation dose-matched SS-DECT (n = 51, 120 kV, split-filter technique, 384 ref. mAs) or DS-DECT (n = 51, 80/Sn150 kV, tube A 100/tube B 67 ref. mAs). Inline default images (DI) and virtual monoenergetic images (VMI) for two different low energies (40 and 60 keV) were reconstructed. Objective image quality was evaluated as dose-normalized contrast to noise ratio (CNRD), and subjective image quality was rated on a 5-point Likert scale. Results: In both groups, highest CNRD values for vessel and tumor attenuation were obtained at 40 keV. DS-DECT was significantly better than SS-DECT regarding vessel and tumor attenuation. Overall subjective image quality in the SS-DECT group was highest on the DI followed by 40 keV and 60 keV. In the DS-DECT group, subjective image quality was highest at 40 keV followed by 60 keV and the DI. Forty kiloelectron volts and 60 keV were significantly better in the DS-DECT compared to the SS-DECT group (both p < 0.01). Conclusions: In split-filter SS-DECT as well as in DS-DECT, highest overall image quality in head and neck imaging can be obtained with a combination of DI and low keV reconstructions. DS-DECT is superior to split-filter SS-DECT in terms of subjective image quality and vessel and tumor attenuation. Key Points: • Image quality was diagnostic with both dual-energy techniques; however, the dual-source technique delivered significantly better results. • Highest overall image quality in head and neck imaging can be obtained with a combination of default images and low keV reconstructions with both dual-energy techniques. • The results of this study may have relevance for the decision-making process regarding replacement of CT scanners and focused patient examination considering image quality and subsequent therapeutic decision-making.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Diagnostic imaging; Head and neck neoplasms; Image enhancement

Computed Tomography of the Head and Neck Region for Tumor Staging-Comparison of Dual-Source, Dual-Energy and Low-Kilovolt, Single-Energy Acquisitions - May, Matthias; Brügel, Joscha; Brand, Michael; Wiesmüller, Marco; Krauss, Bernhard; Allmendinger, Thomas; Uder, Michael; Wüst, Wolfgang (Investigative Radiology, 2017)
The aim of this study was to intra-individually compare the image quality obtained by dual-source, dual-energy (DSDE) computed tomography (CT) examinations and different virtual monoenergetic reconstructions to a low single-energy (SE) scan.Third-generation DSDE-CT was performed in 49 patients with histologically proven malignant disease of the head and neck region. Weighted average images (WAIs) and virtual monoenergetic images (VMIs) for low (40 and 60 keV) and high (120 and 190 keV) energies were reconstructed. A second scan aligned to the jaw, covering the oral cavity, was performed for every patient to reduce artifacts caused by dental hardware using a SE-CT protocol with 70-kV tube voltages and matching radiation dose settings. Objective image quality was evaluated by calculating contrast-to-noise ratios. Subjective image quality was evaluated by experienced radiologists.Highest contrast-to-noise ratios for vessel and tumor attenuation were obtained in 40-keV VMI (all P < 0.05). Comparable objective results were found in 60-keV VMI, WAI, and the 70-kV SE examinations. Overall subjective image quality was also highest for 40-keV, but differences to 60-keV VMI, WAI, and 70-kV SE were nonsignificant (all P > 0.05). High kiloelectron volt VMIs reduce metal artifacts with only limited diagnostic impact because of insufficiency in case of severe dental hardware. CTDIvol did not differ significantly between both examination protocols (DSDE: 18.6 mGy; 70-kV SE: 19.4 mGy; P = 0.10).High overall image quality for tumor delineation in head and neck imaging were obtained with 40-keV VMI. However, 70-kV SE examinations are an alternative and modified projections aligned to the jaw are recommended in case of severe artifacts caused by dental hardware.
EVALuna2:14672